Effects of P-Coumarate 3-Hydroxylase Downregulation on the Compositional and Structural Characteristics of Lignin and Hemicelluloses in Poplar Wood (Populus alba × Populus glandulosa) - Peng, Xiao-Peng; Bian, Jing; Yao, Shuang-Quan; Ma, Cheng-Ye; Wen, Jia-Long (Frontiers in Bioengineering and Biotechnology, 2021)
Elucidating the chemical and structural characteristics of hemicelluloses and lignin in the p-coumarate 3-hydroxylase (C3H) down-regulated poplar wood will be beneficial to the upstream gene validation and downstream biomass conversion of this kind of transgenic poplar. Herein, the representative hemicelluloses and lignin with unaltered structures were prepared from control (CK) and C3H down-regulated 84K poplars. Modern analytical techniques, such as 13C NMR, 2D-HSQC NMR, and gel chromatography (GPC), were performed to better delineate the structural changes of hemicelluloses and lignin caused by transgenesis. Results showed that both the hemicelluloses (H-CK and H-C3H) extracted from control and C3H down-regulated poplar wood have a chain backbone of (1→4)-β-D-Xylan with 4-O-Me-α-D-GlcpA as side chain, and the branch degree of the H-C3H is higher than that of H-CK. With regarding to the lignin macromolecules, NMR results demonstrated that the syringyl/guaiacyl (S/G) ratio and dominant substructure β-O-4 linkages in C3H down-regulated poplar were lower than those of control poplar wood. By contrast, native lignin from C3H down-regulated poplar wood exhibited higher contents of p-hydroxybenzoate (PB) and p-hydroxyphenyl (H) units. In short, C3H down-regulation resulted in the chemical and structural changes of the hemicelluloses and lignin in these poplar wood. The identified structures will facilitate the downstream utilization and applications of lignocellulosic materials in the biorefinery strategy. Furthermore, this study could provide some illuminating results for genetic breeding on the improvement of wood properties and efficient utilization of poplar wood.